Pemberdayaan UMKM Desa Babakan Mulya Kuningan Melalui Pelatihan Pemanfaatan Teknologi Informasi - Irfan Ali; Nining Rahaningsih; Iin (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Babakan Mulya Village in Kuningan Regency is a location that has significant economic potential in the Micro, Small and Medium Enterprises MSME sector. However, this potential has not been fully exploited due to the challenges faced by MSMEs in adopting Information Technology (IT) as a tool to develop their business. Therefore, IT utilization training for MSMEs in Babakan Mulya Village is an important initiative to increase the competitiveness of the local economy. Babakan Mulya Village is located in Kuningan Regency, West Java, Indonesia. This village has a number of MSMEs covering various sectors, such as agriculture, crafts and traditional culinary delights. However, most of these MSMEs face obstacles in adopting. Cases that often occur are the inability to utilize online platforms to market their products, lack of understanding of the importance of IT in business management, and limited access to digital technology. The results of MSME empowerment activities in Babakan Mulya Village, Kuningan through training in the use of information technology, it can be concluded that the implementation Information technology has had a real positive impact on MSMEs and communities in the village. First, the adoption of information technology has increased the operational efficiency of MSMEs. Production processes and inventory management become more structured and efficient, allowing them to meet market demand in a more timely and quality manner. Second, the use of information technology expands market reach. With the ability to market products online, Babakan Mulya Village MSMEs can reach customers in various regions, even at the national level. This opens up new opportunities for business growth and increased revenue.